Prevalence of hypertension and prehypertension in adolescence in Ahvaz, Iran. (December 2017) - Aleali, Armaghan Moravej; Latifi, Seyed Mahmoud; Rashidi, Homeira; Payami, Seyed Peyman; Sabet, Azar
Abstract: Background: High blood pressure is a risk factor for some disease like stroke, coronary heart disease, and renal failure. High blood pressure in children is an increasing health problem. Objectives: The aim of this study was to determine prevalence of hypertension and pre-hypertension age between 10 to 17 years old. Patients and methods: This descriptive analytic study was conducted using multiphase sampling method in Ahvaz (Southwest of Iran). A questionnaire include: height, weight, and body mass index, systolic and diastolic blood pressures filled for each participant. Blood pressure was measured twice for each person. For the diagnosis of hypertension, the fourth report of the Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents of the National Health Institute of United States was used. Results: Total participants of the study were 1707children and adolescents including 922 boys (54%) and 785 girls (46%). The prevalence of high blood pressure was 1.7% (2.5% in boys and 0.8%). The prevalence of pre-hypertension was 9%(7.6% in boys, 10.6% in girls). The mean systolic and diastolic blood pressures increased with increasing body mass index. Conclusions: The prevalence of high blood pressure was found to be lower than other studies in our country. The prevalence of the high blood pressure in boys was significantly higher than girls. This study, like other studies showed high correlation between being overweight and an increase in systolic and diastolic blood pressure.